2016
DOI: 10.1177/1462474516670153
|View full text |Cite
|
Sign up to set email alerts
|

Pre-trial detention and guilty pleas: Inducement or coercion?

Abstract: This article examines why accused persons in pre-trial detention decide to plead guilty. Relying on the understanding of coercion proposed by Brunk, the article go beyond his analysis to show how pre-trial detention can exert pressure on an accused individual, who then feels coerced into pleading guilty. Interviews with 12 accused and 12 lawyers showed that in certain situations pre-trial detention can be a source of coercion, particularly if there are lengthy procedural delays and eventual sentences can be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 18 publications
(40 reference statements)
1
36
0
Order By: Relevance
“…Although the accused in this profile mention similar pressures, we also found pressures that were cited only in a limited number of cases but greatly affected decision making and accused individuals’ impressions of having been coerced to plead guilty. The financial cost of going to trial was an important constraint for Theresa and Jean, and pretrial detention or having to do “dead time 10 ” was also brought up by some of the accused (see Euvrard and Leclerc 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the accused in this profile mention similar pressures, we also found pressures that were cited only in a limited number of cases but greatly affected decision making and accused individuals’ impressions of having been coerced to plead guilty. The financial cost of going to trial was an important constraint for Theresa and Jean, and pretrial detention or having to do “dead time 10 ” was also brought up by some of the accused (see Euvrard and Leclerc 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The practice of overcharging is defined as charging the accused with every charge that is legally possible, even when it is evident that conviction on some of the counts is unlikely or unnecessary. This practice has been documented in Canada by Klein (1976) and Ericson and Baranek (1982), but a recent study (Euvrard & Leclerc 2015) confirms that it is still used by some Crown attorneys to increase their bargaining power during negotiations.…”
mentioning
confidence: 83%
“…The desire to avoid this potential loss of employment and economic hardship, along with the inability to pay bail, often triggers guilty pleas (Rabinowitz ; Natapoff ; Pelvin ), and numerous studies have found that pretrial detention negatively affects case outcomes (for recent reviews, see Jones ; Schlesinger ; Lee ; Stevenson ; Menefee ; Dobbie, Goldin, and Yang ). Pretrial detainees plead guilty more quickly (Sacks and Ackerman ), accepting less advantageous plea deals compared to those arising from lengthier plea negotiations (Kellough and Wortley ; Cheng ; Euvrard and Leclerc ). These effects may be especially pronounced in lower‐level cases because the procedural costs of fighting the charges often outweigh any formal sanctions a defendant might receive if convicted, leading many misdemeanants to plead guilty to get out of jail (Feeley ; Heaton, Mayson, and Stevenson ; Kohler‐Hausmann ; Petersen , ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The specification of Z and X parameters in Y 1 and Y 2, respectively, refers to exogenous variables and excludes variables over which defendants or prosecutors exercise control. For example, although detention and bail status may influence defendants' decisions on plea bargaining (Euvrard and Leclerc 2017;Kellough and Wortley 2002), such variables are just as endogenous as plea bargaining itself. It would only be legitimate to include detention status in Z if its latent variable is independent of y 2 , i.e.…”
Section: Appendix 3: Pre-trial Detention and Other Endogenous Variablesmentioning
confidence: 99%